EFEKTIVITAS PROSES PEMBUATAN LAPORAN PERTANGGUNG JAWABAN BENDAHARA PENGELUARAN DENGAN SILABI - Kemas Welly Angga Permana (Jurnal AkunStie (JAS), 2020)
This study aims to determine the process of making a treasurer accountability report at the BPKP Representative Office of South Sumatra Province. The research design used is associative quantitative. With indicators in accordance with Law Number 17 of 2003 concerning State Finances Article 35 paragraph (2); Regulation of the Minister of Finance Number 190 / PMK.05 / 2012 concerning the Position and Responsibility of the Treasurer; and Regulation of the Director General of Treasury Number 03 / PB / 2014 article 3 paragraph 7 states that all revenues and expenditures as referred to in Article 30 paragraph 1 shall be made with the SILABI application. The results showed that, the LPJ treasurer-making process was in accordance with the guidelines for the money it managed. At the BPKP Representative Office for the Province of South Sumatra, they only appoint an Expenditure Treasurer, to manage finances based on the Budget Activity Plan (RKA). Experience, certification, workload and welfare attached to the Expenditure Treasurer are in accordance with regulations. Application of the Agency Treasury Report System (SILABI) updated version 19.0.5. dated 20 May 2019, available and easy to download, use friendly, and there are instructions for use. Thus, the making of the Accountability Report (LPJ) of the spending treasurer is in accordance with statutory regulations, efficient, economical, effective and transparent to report.